The diversity of endophytic fungi in Tartary buckwheat (Fagopyrum tataricum) and its correlation with flavonoids and phenotypic traits - Chen, Meiqi; Ding, Ziqi; Zhou, Min; Shang, Yukun; Li, Chenglei; Li, Qingfeng; Bu, Tongliang; Tang, Zizhong; Chen, Hui (Frontiers in Microbiology, 2024)
Tartary buckwheat (Fagopyrum tataricum) is a significant medicinal crop, with flavonoids serving as a crucial measure of its quality. Presently, the artificial cultivation of Tartary buckwheat yields low results, and the quality varies across different origins. Therefore, it is imperative to identify an effective method to enhance the yield and quality of buckwheat. Endophytic fungi reside within plants and form a mutually beneficial symbiotic relationship, aiding plants in nutrient absorption, promoting host growth, and improving secondary metabolites akin to the host. In this study, high-throughput sequencing technology was employed to assess the diversity of endophytic fungi in Tartary buckwheat. Subsequently, a correlation analysis was performed between fungi and metabolites, revealing potential increases in flavonoid content due to endophytic fungi such as Bipolaris, Hymenula, and Colletotrichum.Additionally, a correlation analysis between fungi and phenotypic traits unveiled the potential influence of endophytic fungi such as Bipolaris, Buckleyzyma, and Trichosporon on the phenotypic traits of Tartary buckwheat. Notably, the endophytic fungi of the Bipolaris genus exhibited the potential to elevate the content of Tartary buckwheat metabolites and enhance crop growth. Consequently, this study successfully identified the resources of endophytic fungi in Tartary buckwheat, explored potential functional endophytic fungi, and laid a scientific foundation for future implementation of biological fertilizers in improving the quality and growth of Tartary buckwheat.